2021
DOI: 10.1111/1747-0080.12704
|View full text |Cite
|
Sign up to set email alerts
|

Is there enough behaviour change science in nutrition and dietetics curricula in Australia and New Zealand? A descriptive study

Abstract: The application of behaviour change science is fundamental to the role of dietitians. This study aimed to describe how behaviour change science is embedded within the curricula of accredited/registered dietetics programs in Australia and New Zealand.Methods: A descriptive study triangulated quantitative document analysis of curricula content from university websites (Part 1) with qualitative, structured interviews with dietetics academics (Part 2). Part 2 verified and advanced upon information captured in Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
(50 reference statements)
1
13
0
Order By: Relevance
“…8 A further study describing how behaviour change is embedded in pre-registration dietetic programmes in Australia and New Zealand reported that communication skills were a component of all programmes but the content varied. 9 Similar findings were reported in an analysis of how the clientdietitian relationship is embedded in dietetic programmes. 10 In addition, dietitians have expressed some dissatisfaction with their training in communication skills [11][12][13] underlining the need for more consistent educational approaches.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…8 A further study describing how behaviour change is embedded in pre-registration dietetic programmes in Australia and New Zealand reported that communication skills were a component of all programmes but the content varied. 9 Similar findings were reported in an analysis of how the clientdietitian relationship is embedded in dietetic programmes. 10 In addition, dietitians have expressed some dissatisfaction with their training in communication skills [11][12][13] underlining the need for more consistent educational approaches.…”
Section: Introductionsupporting
confidence: 72%
“…Communication skills teaching was found to be consistently included in dietetic education programmes in two Australian analyses of curriculum documentation and dietetic educator perspectives. 9,10 How this was delivered and embedded in the wider context of behaviour change science and building effective dietitian-patient therapeutic relationships was highly variable. 9,10 The teaching that dietitians received in communication skills as part of their pre-registration education was explored in five studies.…”
Section: Inclusion Of Communication Skills Education In Dieteticsmentioning
confidence: 99%
“…Dietitians in the United Kingdom and Australia believe behaviour change is fundamental to the practice of dietetics. 27,28 In Canada, there is a prioritisation of science-based knowledge 29 and behaviour change models rooted in individualised changes and motivational factors. 30 Such models often fail to fully recognise the systemic economic, political, and social factors (such as stigma) that can make behaviour change next to impossible for some individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Dietitians are trained to design and implement food and nutrition programs that help clients to change or modify some part of their diet, their eating behaviours, their bodies, and improve their health. Dietitians in the United Kingdom and Australia believe behaviour change is fundamental to the practice of dietetics 27,28 . In Canada, there is a prioritisation of science‐based knowledge 29 and behaviour change models rooted in individualised changes and motivational factors 30 .…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important given Rigby et al 40 found dietary interventions based on behaviour change theory and techniques were potentially more effective at improving patient health outcomes than interventions without theoretical underpinnings. While behaviour change science is valued by the dietetic profession, 46 we encourage embedding and documenting behaviour change theory in dietetic practice to improve patient‐centred care.…”
Section: Discussionmentioning
confidence: 99%